Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/np500555k
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Structure Elucidation, Relative LC-MS Response, and in Vitro Toxicity of Azaspiracids from the Dinoflagellate Azadinium spinosum

Abstract: /npsi/ctrl?action=rtdoc&an=21274921&lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=21274921&lang=fr READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 42 publications
(104 reference statements)
1
65
0
Order By: Relevance
“…Compared to other Amphidomataceae species, for which only a few azaspiracids have been reported, the diversity of AZAs in the Mediterranean A. dexteroporum strain seems to be exceptional. However, a high diversity of AZAs is now also known from A. spinosum [17,29] and future studies using the multi-platform approach or computational approaches such as molecular networking [31] might show this for other species/strains as well. The presence of so many AZAs is even more surprising if compared to the complete absence of AZAs in the Arctic strain of the same species [27], although cases of intraspecific differences in toxin profiles are widespread [14,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to other Amphidomataceae species, for which only a few azaspiracids have been reported, the diversity of AZAs in the Mediterranean A. dexteroporum strain seems to be exceptional. However, a high diversity of AZAs is now also known from A. spinosum [17,29] and future studies using the multi-platform approach or computational approaches such as molecular networking [31] might show this for other species/strains as well. The presence of so many AZAs is even more surprising if compared to the complete absence of AZAs in the Arctic strain of the same species [27], although cases of intraspecific differences in toxin profiles are widespread [14,32].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the toxicity of some purified AZA analogues relative to AZA-1 showed that all analyzed AZAs were toxic and that AZA-2, AZA-3, and AZA-6 were more toxic than AZA-1 by 8.3, 4.5, and 7 times, respectively [10], 37-epi-AZA-1 was 5 times more toxic [11], AZA-33 and AZA-34 were 5 times less toxic and 5 times more toxic, respectively [17], and AZA-36 and AZA-37 were 6 and 3 times less toxic, respectively [15]. As major differences in toxicity can be related to slightly different structures of AZAs, the actual toxicity of the different compounds produced by the Mediterranean A. dexteroporum is worthy of consideration in future toxicological studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6-9 AZA1, 1, (Figure 1) is a K + channel blocker, 10 and is highly cytotoxic to multiple cell types which undergo atypical apoptosis after exposure. 11 AZAs were first identified in the late 1990s and since then more than 30 analogues have been observed in shellfish, 12 phytoplankton, [13][14][15] crabs 16 and a marine sponge. 17 Only 1, AZA2, 2, and AZA3, 3, (Figure 1) are currently regulated in raw shellfish.…”
Section: Introductionmentioning
confidence: 99%
“…This practice is acceptable if relative molar responses (RMRs) between analogs have been assessed. Studies evaluating response factors for toxins have been limited, but a recent study highlighted that RMRs for AZAs were dependent both on chromatographic and MS acquisition parameters . There is lack of knowledge concerning response factors for other regulated toxins including OA/DTXs, the PTXs, the YTXs and the cyclic imines.…”
Section: Introductionmentioning
confidence: 99%